IMMIGRATION INSIGHTS EDUCATION AND THE UTILIZATION OF FOREIGN REPORTING APPLICATIONS (APOA) IN THE REGION OF THE CLASS I IMMIGRATION OFFICE SPECIAL NON TPI JAKARTA SELATAN FOR RAGUNAN Senior High School Students - M. Alvi Syahrin; Ridha Nikmatus Syahada (Polteknik Imigrasi, 2020)
This activity is motivated by the low level of public knowledge, especially students, regarding immigration, which includes the functions of passports and supervision of foreigners. The purpose of this activity is to fulfill community service duties by cadets who are carrying out PPL and KKN activities at the Class I Special Immigration Office for Non-TPI South Jakarta, as well as to increase the knowledge of Ragunan State Senior High School students about immigration. This activity uses a qualitative approach with a descriptive research method where the research is held at SMA Negeri 1 Ragunan which is located in the Ragunan Gor Complex, Ragunan, Pasar Minggu, South Jakarta, the Special Capital Region of Jakarta. The results of this study found that the knowledge of students related to immigration can be said to be quite low so that it requires more education on various cases in the immigration sector as well as knowledge about the active role of the community to help immigration authorities in monitoring foreigners by providing information and data. Accurate.